Strengthening Cross-Border Value Chains : Opportunities for India and Bangladesh - Kathuria, Sanjay; Mathur, Priya (Washington, DC: World Bank, 2019)
It is widely agreed that, over the past decade, accelerating infrastructure investments in India's North Eastern Region (NER) and neighboring countries, along with connectivity agreements with Bangladesh, hold immense promise for unlocking NER's economic potential. Other global trends, such as the growing incomes and consumer awareness in India and neighboring countries; a rising preference for fresh, healthy, safe, environmentally friendly, and socially responsible products; the growing role of services in manufacturing; and increasing demand for skilled resources are also very favorable for NER. Together, these developments can help NER showcase its strengths in agriculture and services, thereby developing value chains in these sectors, which will lead to sustainable, better-paying, job opportunities for the people of NER.